Methods for overcoming dormancy and seed storage of Enterolobium contortisiliquum - Denes Ferraz; Werther Pereira Ramalho; Luís Sérgio Rodrigues Vale (Acta Scientiarum: Agronomy, 2019)
The production of forest species that present seedlings with exogenous dormancy is limited by low germination rates, which can be overcome by rupturing or weakening the tegument. This study aimed to evaluate the efficiency of low-cost methods of overcoming dormancy and determine the effect of storage on the seeds of Enterolobium contortisiliquum. Four storage periods were used, freshly collected seeds (0), stored for 6, 12 and 18 months, and four methods were applied, mechanical scarification and immersion in water (EI), mechanical scarification (ES), immersion in water (IM) and control (TE). We obtained the percentage values of seedling emergence (EP) and the mean emergence time (TME). Conductivity and moisture were obtained as indicators of the physical and physiological quality of seeds, respectively. Variations in moisture content and electrical conductivity during storage did not have effect on the percentage of germination. EI treatment was more efficient for overcoming dormancy than the ES was, regardless of storage time. IM and TE treatments did not lead to germination. EI was the most efficient treatment for decreasing the TME. The results indicate that alternative and low-cost methods are efficient at overcoming exogenous dormancy and thus can be used to optimize the process of seedling production.